STATISTICAL METHODS AS A BASIS OF MARKETING INVESTIGATIONS - V. Bogdanova; M. Bogdanova; L. Parshintseva (Вестник университета)
The assesses the volume and dynamics of marketing research in Russia over the past ten years which are one of the most interesting and popular marketing tools has been done. The comparative analysis of market research volume dynamics with the dynamics of the main macroeconomic indicators in comparable prices has been performed. The role of statistical methods in marketing research has been analyzed, the brief description has been given, and provides recommendations for using of computer technology to solve analytical problems has been done.